(untitled) (Research, Society and Development, 2021)
Objective: To describe the actions taken by nursing professionals in the care services of people living with HIV. Methodology: Cross-sectional field study, quantitative, based on the attributions of the nursing team in the HIV/AIDS Care Program of Brazil. Twelve Brazilian cities distributed in five brazilians geographic regions were studied. Data were collected with 54 managers from health units through a standardized questionnaire. The variables analyzed was activities and professionals responsible for carrying out care actions for people living with HIV. Results: Of the 54 institutions studied, 18.5% are in the North region, 16.7% in the Northeast, 14.8% in the Midwest, 46.3% in the Southeast and 3.7% in the South. Among the activities assigned to the nursing team, nurses were mentioned as responsible for individual and collective counseling activities (77.9 and 73.4%), HIV testing offer (74.5%), nursing consultation (95.1%), first consultation with clients with HIV (88.5%) and home care (84.6%). The performance of psychological and social care was pointed out as the nurses’ own activity, despite being the competence of other professionals; in addition to exclusive nurses’ actions being assigned to nursing technicians and assistants, such as nursing consultations. Conclusion: Most of the actions performed in the services were associated with nurses. This association demonstrates the recognition of the importance of this professional by the managers, but also little clarity about the attributions of the nursing team revealing a managerial weakness of health teams.